Memorandum of understanding between Faculty of Pharmacy, Universiti Teknologi MARA, Malaysia and Graduate School of Pharmaceutical Sciences, Tokyo University of Science, Japan / Fakulti Farmasi - Universiti Teknologi MARA, Fakulti Farmasi (Universiti Teknologi MARA (UiTM), 2018)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.